2008
DOI: 10.3390/ijms9040554
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Select Fumonisin Forming Fusarium Species Using PCR Applications of the Polyketide Synthase Gene and its Relationship to Fumonisin Production in vitro

Abstract: A polymerase chain reaction (PCR) based diagnostic assay was used to develop markers for detection of Fusarium verticillioides (=F. moniliforme), a fumonisin producing fungus in maize tissues. Species-specific primers were designed based on sequence data from the polyketide synthase (PKS) gene (FUM1-previously FUM5) responsible for fumonisin production in fungi. Four sets of oligonucleotide primers were tested for their specificity using 24 strains of F. verticillioides, 10 F. proliferatum, and 12 of other Fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 59 publications
0
29
1
Order By: Relevance
“…The presence of FUM1, by PCR amplification, was used to narrow down the fungal isolates to be studied here from the Fusarium collections initially selected based only on colony characteristics. However, it cannot validate the species identification within the G. fujikuroi species complex because no species-specific amplification of FUM1 has been achieved (Baird et al, 2008;Jurado et al, 2010). Moreover, the usefulness of the species-specific primers sets used in this study was limited because they showed no specificity in some isolates (data not shown), as described previously (Kang et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…The presence of FUM1, by PCR amplification, was used to narrow down the fungal isolates to be studied here from the Fusarium collections initially selected based only on colony characteristics. However, it cannot validate the species identification within the G. fujikuroi species complex because no species-specific amplification of FUM1 has been achieved (Baird et al, 2008;Jurado et al, 2010). Moreover, the usefulness of the species-specific primers sets used in this study was limited because they showed no specificity in some isolates (data not shown), as described previously (Kang et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Theoretically, Fusarium mycotoxins can be produced on every plant and all plant parts infested by toxigenic Fusarium species. Over the last ten years, detection of mycotoxins and toxigenic Fusarium species has advanced signifi cantly with the development of PCR-based techniques (13)(14)(15)(16). However these techniques are still not widely used because they are expensive.…”
Section: Discussionmentioning
confidence: 99%
“…PCR using species-specific primers ( Table 1) was used to identify the principal Fusarium species of maize (e.g., F. verticillioides, F. proliferatum, F. subglutinans, and F. graminearum). PCR using the FUM5F and FUM6R primer pair was performed to determine whether or not the FUM1 gene was present (Baird et al 2008). PCR, using the Gfmat1a/Gfmat1b and Gfmat2c/Gfmat2d primer pairs, was used to identify the mating type (MAT-1 or −2) of F. verticillioides strains (Steenkamp et al 2000).…”
Section: Dna Extraction and Pcr Assaysmentioning
confidence: 99%